A Regional General Equilibrium Model of the United States: Tax Effects on Factor Movements and Regional Production - Morgan, William; Mutti, John; Partridge, Mark (The Review of Economics and Statistics, 1989)
William Morgan, John Mutti, Mark Partridge, A Regional General Equilibrium Model of the United States: Tax Effects on Factor Movements and Regional Production, The Review of Economics and Statistics, Vol. 71, No. 4 (Nov., 1989), pp. 626-635